(untitled) (Journal of Entrepreneurship and Business, 2022)
Economic growth is very important for all countries, one way to increase economic growth is to invest in both Domestic Investment (PMDN) and Foreign Investment (PMA). This study aims to analyze the effect of investment on economic growth in the Province. This research is quantitative research using secondary data from the Central Statistics Agency of the Republic of Indonesia, especially in the Province of Riau. The study results show that foreign investment and domestic investment, as well as several superior business sectors in Riau province, basically increase gross domestic product, which means it affects the economic growth of Riau province. The hope is that there is a need for coordination and a clear division of tasks and responsibilities between government units in districts in Riau Province to improve infrastructure services. Carry out a reform agenda in regional regulations. It is necessary to form an official investor forum and be carried out regularly, and Provincial and district governments should integrate policies and investment development programs (investment) following sectors/sub-sectors and highly competitive commodities in the region.